Order for payment procedure and interruption of procedural periods for the pandemic created for the Covid-19. On purpose of the CJEU Judgment of 15 September of 2022 C-18/21, Uniqa Versicherungen AG c. VU - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The main purpose of this paper is to analyze the CJEU judgment of September 15, 2022, C-18/21, Uniqa Versicherungen AG v. VU. This resolution is the last that the CJEU has established in relation to Regulation 1896/2006, which regulated the European order for payment process. In response to a prejudicial question referred by the Austrian Supreme Civil and Criminal Court, the CJEU must decide whether an Austrian national Law that interrupted the procedural periods for civil proceedings in Austria could also be applied to the European order for payment procedure. The CJEU, based on the principle of procedural autonomy of the Member States, resolves this issue positively.
Keywords: order for payment procedure; principle of procedural autonomy; Covid-19; interruption of procedural periods